(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Nitrobenzene-based flowering stimulants are rare causes of fatal poisoning. This case highlights acute methemoglobinemia due to ingestion of a stimulant, describing clinical, autopsy, and toxicological findings.